2020
DOI: 10.3390/molecules25225373
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Cycloaddition to the Bay Region of Perylene and Its Derivatives as an Attractive Strategy for PAH Core Expansion: Theoretical and Practical Aspects

Abstract: PAHs (polycyclic aromatics hydrocarbons), the compound group that contains perylene and its derivatives, including functionalized ones, have attracted a great deal of interest in many fields of science and modern technology. This review presents all of the research devoted to modifications of PAHs that are realized via the Diels–Alder (DA) cycloaddition of various dienophiles to the bay regions of PAHs, leading to the π-extension of the starting molecule. This type of annulative π-extension (APEX) strategy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 194 publications
(474 reference statements)
0
7
0
Order By: Relevance
“…Namely, LUMO for COOMe is located lower, but steric hindrance is higher for Ph than COOMe. Analogically, we observed that the influence of electron and steric factors are quite similar to the DA cycloaddition to the perylene bay region [ 54 , 55 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 77%
See 2 more Smart Citations
“…Namely, LUMO for COOMe is located lower, but steric hindrance is higher for Ph than COOMe. Analogically, we observed that the influence of electron and steric factors are quite similar to the DA cycloaddition to the perylene bay region [ 54 , 55 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 77%
“…Again, the highest reactivity of acetylene with two COOMe groups is worth noting. This is undoubtedly the effect of LUMO energy decrease [ 54 , 55 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[280] In this work, BPTI was the only dye to be prepared by cycloaddition of maleic anhydride to the perylene bay region of perylene diimide. [281,282] Figure 17. Chemical structures of PTCTE, BPTI and DPPDI, the different monomers and additives.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…21 When treated with suitable dienophiles in the presence of an oxidative reagent, π-extension takes place. 22 In this context, perylene is the suitable platform for the ODA reaction as it poses two bay positions (Scheme S1, ESI†). When perylene is treated with maleic anhydride in the presence of p -chloranil, π-extended benzoperylene anhydride is obtained in 10 min.…”
mentioning
confidence: 99%